Tools implementation in management of continuous improvement processes - Martins, Mariana Alves (2019)
Technological development and pressure to meet customer requirements through high productivity and low costs forces companies to be extremely flexible and efficient. For this purpose, many organizations have been adopting continuous improvement strategy which promotes constant insertion of small incremental improvements and better results in regard of efficiency and quality. The aim of this paper is to show how a company has progressed its continuous improvement of management processes. This was successfully achieved through new tools developed to solve different problems in distinct dimensions regarding continuous improvement. The developed tools were database systems and it was possible to realise their positive impact in continuous improvement of management processes in the focused company were they were implemented, since they established access to consistent data and did enable to reduce redundant information spread across multiple files and software tools, and thus eliminating waste. Moreover, these new tools developed allowed to pass from traditional and manual recorded methods to computerized systems, making information more accessible and always updated. Thus connection between information systems and management of continuous improvement processes is essential for companies’ evolution and success.